Non-radical, stepwise complete endoscopic resection of Barrett’s epithelium in short segment Barrett’s esophagus has a low stricture rate - Andreas Koutsoumpas (Endoscopy International Open, 2016)
Background and aims: Radical endoscopic excision of Barrett’s epithelium performing 4 – 6 endoscopic resections during the same endoscopic session results in complete Barrett’s eradication but has a high stricture rate (40 – 80 %). Therefore radiofrequency ablation is preferred after endoscopic mucosal resection (EMR) of visible nodules. We investigated the clinical outcome of non-radical, stepwise endoscopic mucosal resection with a maximum of two endoscopic resections per endoscopic session. Methods: We analysed our prospectively maintained database of patients undergoing esophageal EMR for early neoplasia in Barrett’s esophagus from 2009 to 2014. EMR was performed using a maximum of two band ligation mucosectomies per endoscopic session; thereafter, follow-up was 3-monthly and EMR was repeated as required for Barrett’s eradication. Results: In total, 118 patients underwent staging EMR for early Barrett’s neoplasia. Subsequently, 27 patients underwent surgery/chemotherapy due to deep submucosal or more advanced tumor stages or were managed conservatively. The remaining 91 patients with high grade dysplasia (48), intramucosal (38) or submucosal cancer (5) in the resected nodule underwent further endoscopic therapy with a mean follow-up of 24 months. Remission of dysplasia/neoplasia was achieved in 95.6 % after 12 months treatment. Stepwise endoscopic Barrett’s resection resulted in complete Barrett’s eradication in 36/91 patients (39.6 %) in a mean of four sessions; 40/91 patients (44.0 %) had a short circumferential Barrett’s segment (< 3 cm). In this group, repeated EMR achieved complete Barrett’s excision in 85.0 %. One patient developed a stricture (1.1 %), one a delayed bleeding, and there were no perforations. Conclusion: In patients with a short Barrett’s segment, non-radical endoscopic Barrett’s resection at the time of scheduled endoscopy follow-up allows complete Barrett’s eradication with very low stricture rate.